Sentiments Analysis on Twitter Towards Hoax Information on Social Media News - Ansar Suherman; Ferdi Ferdi; Harry Fajar Maulana; Muhammad Rizal Ardiansah Putra (Jurnal Ilmu Komunikasi, 2024)
Hoaxes are a perilous byproduct of huge technology advancements, particularly the rise of social media. Using Twitter as an example, it is one of the most popular social media platforms for information sharing, communication, and entertainment. As a consequence, Twitter users may readily propagate fake or hoax information. The aim of this study is to find public opinion about hoaxes derived from Twitter user conversations around COVID-19. This study makes use of Twitter data obtained from Drone Emprit Academic. This study examined all processed tweets and surveyed public opinion on "Hoaks" (including mentions, retweets, and replies). The DEA engine analyzes the word frequency and mood of Twitter users to determine if a predominant emotion is good, negative, or neutral. According to the study results, netizens remarked on the COVID-19, alleging that the appearance of the Delta type variation was caused by the vaccination, not the virus. They do not regularly check facts owing to boredom, laziness, and reliance on just one source of information verification. Furthermore, only information that corresponds to their interests and needs will be approved. Thus, via discourse about Hoax, social media allows the formation of a platform for mutual understanding, sharing, and dynamically debating the meaning of demonstrations. This research provides a contribution to the disclosure of information about public opinion towards a discourse discussed on Twitter with the help of a DEA engine.